Etiology of developmental spinal stenosis: A genome‐wide association study. Issue 4 (17th October 2017) - Cheung, Jason P. Y.; Kao, Patrick Y. P.; Sham, Pak; Cheah, Kathryn S. E.; Chan, Danny; Cheung, Kenneth M. C.; Samartzis, Dino
ABSTRACT: Our study aimed to identify possible single nucleotide polymorphisms (SNPs) via a genome‐wide association study (GWAS) approach and a candidate gene platform that were associated with lumbar developmental spinal stenosis (DSS). Southern Chinese population‐based study volunteers were assessed (age range: 18–55 years). DSS was defined as the anteroposterior bony spinal canal diameter on T1‐weighted axial MRI of L1 to S1. Genotyping was performed using the Illumina HumanOmniZhongHua‐8 BeadChip. Using the canal diameter as the quantitative trait, genomic statistical analyses was performed. A total of 469 subjects were recruited. The mean axial AP measurements noted were: L1: 21.8 mm, L2: 21.9 mm, L3: 22.4 mm, L4: 20.2 mm, L5: 19.6 mm, and S1: 17.3 mm. Q–Q plots of genome‐wide associations found significant differences in L4 and L5 measurements. More significant SNPs were found on chromosomes 8, 11, and 18. Low‐density lipoprotein receptor‐related protein 5 on chromosome 11 was found to be an important functional gene in canal bony development via candidate gene approach. We found two clusters in the findings with one including the upper levels (L1–L4) and the other the lower levels (L5 and S1). This is the first GWAS addressing DSS. The presence of multiple SNPs suggests a multi‐factorial origin of DSS. Further analyses noted region‐specific genetic predisposition, delineating distinct upper to lower lumbar regions of DSS. With better understanding of the DSS phenotype and genetic markers, the at‐risk population can be identified early, preventative measures can be initiated, lifestyle/activity modification can be implemented, and more novel and precision‐based therapeutics can be developed. © 2017 Orthopaedic Research Society. Published by Wiley Periodicals, Inc. J Orthop Res 36:1262–1268, 2018.